芬蘭小學職前教師素質管理機制之探究 Primary Pre-teacher Quality Management System in Finland - 廖容辰 Liao, Jung-Chen (National Changhua University of Education, 2010)
近年來，師資培育的改革一直是我國的發展重點之一。首先，自1994 年師資培育法公佈後，我國的師資培育進入百家爭鳴的時期。但多元而開放的師資培育管道，如今卻面臨品質低落之虞。故2006 年、2009 年，教育部相繼提出教師素質的提升方案，致力於教師素質的管理。而芬蘭頂著PISA 冠軍的光環，成為許多國家教育借鏡的對象。其中，高素質的教師是芬蘭國內一致認同的國際評比成功因素。因此，本文擬探討芬蘭小學職前教師素質的管理機制，瞭解芬蘭在職前教師素質管理方面的措施與方法。基此，本文首先針對「教師素質管理」之定義與內涵作一說明。其次，分析芬蘭的師資培育如何透過學生篩選、課程組織與安排，以及師資培育之評鑑等手段，達成職前教師素質的管理。最後，本文提出結論，供國內借鏡參考。 Recently, the reform of teacher education had become the main point of Taiwan. From the establishment of the Teacher Education Act of 1994, teacher education stepped into the multiple period. But the new system now face big challenge of quality decreasing. Therefore, the Government announced the programme of promoting the teacher education quality and teacher quality in 2006 and 2009. And Finland, which was the champion of the PISA in 2000, 2003 and 2006, had become the model of other countries, also explained that high quality teachers were the main factor of the PISA success. Hence, this paper will analyze the teacher quality management of Finland, to understand how Finland educated the high quality teacher through teacher education. To accomplish this, first, the definition of "teacher quality management" will be explored. Second, the process of student selection, the structure of study module, the qualification and the evaluation of teacher education will be described. Finally, some findings will carry out for recommendations for better teacher education and teacher quality management in Taiwan.